Effect of Integrated nutrient management on growth and yield of fennel (Foeniculum vulgare) - KUMAR, VIKASH; SINGH, PARMINDER; MALIK, T P; KUMAR, VINOD; RICHA, RICHA; SHARMA, NEHA; KUMAR, AJAY (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted during the rabi 2016–17 and 2017–18 at Research Farm of CCS Haryana Agricultural University, Hisar. It comprised 16 treatment levels of fertilizer in randomized block-design with three replications. Growth parameters of fennel (Foeniculum vulgare Mill.) crop were significantly affected by the fertilizer treatments. Maximum plants height (16.49, 41.53, 106.13 and 177.00), number of primary branches (1.65, 5.27, 11.50 and 15.34) and number of secondary branches (2.98, 13.18 and 28.97) at 30, 60, 90 days after sowing and at harvest were observed in treatment T11: RDF (100%) + Azotobacter + PSB. Days to 50% flowering ranged from 126.1 (T11) RDF (100%) + Azotobacter + PSB to 119.8 (T16) control. A maximum number of days to maturity were recorded in T11: Recommended dose of fertilizer along with Azotobacter+ PBS (171.6 days) and minimum were under control conditions (T16) i.e. 147.8. Yield attributes like the number of umbels per plant (57.57), umbelets per umbel (33.33), seeds per umbel (613.67), seeds per umbelets (30.52), seed yield per plant (74.93), seed yield (2039.9 kg/ha), biological yield (6965 kg/ha), harvest index (32.08) etc. were highest in treatment T11: RDF (100%) + Azotobacter + PSB per hectare.